The Narrated Materials & Interpretations Attributed to Mu'adh bin Jabal (May Allah be pleased with him), Based on the Interpretations of Tabari and Ibn Abi Hatim - Alshouibi, Mohammad Ali (Journal of Islamic Sciences, 2019)
The purpose of the research is to collect the narrated materials and interpretations attributed to the great Companion Mu'adh bin Jabal (May Allah be pleased with him), based on the interpretations of Tabari and Ibn Abi Hatim.The research difficulty lies in extracting the narrated materials that were quoted from this great Companion and judging them through studying attribution.The research focuses on two issues:The first one is: the profile of the great Companion Mu'adh bin Jabal (May Allah be pleased with him), and his most prominent disciples, who quoted from him.The second one is: Collecting the narrated materials and interpretations attributed to Mu'adh bin Jabal (May Allah be pleased with him), based on the interpretations of Tabari and Ibn Abi Hatim, and highlighting the results of this research.The historical, inductive, and analytical approach has been followed to reach the research objectives.The following results has been reached:Mu'adh bin Jabal (May Allah be pleased with him) has a great status with the Messenger of Allah, Muhammad (Peace be upon him) and his companions.He narrated only few Hadith of the Messenger of Allah, Muhammad (Peace be upon him) in general, and his narrated materials that were mentioned in Tafseer are too few and most of them are weak, which is mostly due to unconnected attribution.Researchers are recommended to collect the sayings and narrated materials of Mu'adh bin Jabal (May Allah be pleased with him) in the Tafsir (Interpretation) books.
Keywords: The Narrated Materials & Interpretations; Mu'adh bin Jabal; May Allah be pleased with him; Interpretation of Tabari; Interpretation of Ibn Abi Hatim; Judgment of attribution